CDR/IPDR ANALYSER AND VISUALIZER: ENHANCING INVESTIGATIVE CAPABILITIES THROUGH COMMUNICATION DATA ANALYSIS - Kapri, Prashant; Thanvi, Noopur; Patane, Shubham; Thakur, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Call Detail Records (CDRs) and Internet Protocol Detail Records (IPDRs) provide a wealth of metadata crucial for modern investigations. With increasing data volumes and complexities, law enforcement agencies (LEAs) require robust tools that can ingest, analyse, and visualize these records. This review paper explores the current landscape of CDR/IPDR analysis tools, their capabilities in criminal investigations, technological approaches for visual analytics, and the challenges associated with handling such sensitive data. Emphasis is placed on the development of an intuitive visualizer that supports multi-format uploads, communication link mapping, suspect prioritization, and exportable reports.